Difficult conversations : how to discuss what matters most - Stone, Douglas, 1958-; Heen, Sheila; Patton, Bruce (New York : Portfolio/Penguin Books, 2011)
From the Harvard Negotiation Project, the organization that brought readers 'Getting to Yes, Difficult Conversations' provides a step-by-step approach to having those tough conversations with less stress and more success. This edition includes a new chapter.
Sort out the three conversations -- Stop arguing about who's right: explore each other's stories -- Don't assume they meant it: disentangle intent from impact -- Abandon blame: map the contribution system -- Have your feelings (or they will have you) -- Ground your identity: ask yourself what's at stake -- What's your purpose?: when to raise it and when to let go -- Getting started: begin from the third story -- Learning: listen from the inside out -- Expression: speak for yourself with clarity and power -- Problem-solving: take the lead -- Putting it all together -- Ten questions people ask about difficult conversations -- A road map to Difficult conversations.
'With a foreword by Roger Fisher'--Cover.
'Updated with answers to the 10 most frequently asked questions about difficult conversations'--Cover.
First published in the U.S.A. by Viking Penguin, 1999.
Keywords: Interpersonal communication; Interpersonal communication -- Case studies; Communication; Interpersonal relations